Application of RNA interference to create lines of Triticum aestivum with improved economic and valuable traits - Brylenko, H.S.; Komisarenko, A.H. (Problems of Environmental Biotechnology, 2023)
Obtaining lines of Triticum aestivum L., with an improved genetic background that will be more tolerant to biotic and abiotic stresses is possible thanks to the use of RNA interference technology, which can lead to a decrease in the expression of the gene of interest. Biotechnological wheat plants with a partially suppressed proline dehydrogenase gene accumulate more proline and are characterized by an increased level of resistance to environmental stresses, which correlates with better productivity.